Nocaviogua A and B: two lipolanthines from root-nodule-associated Nocardia sp. - Chang, Shanshan; Luo, Yajun; He, Ning; Huang, Xinyue; Chen, Mingxu; Yuan, Lijie; Xie, Yunying (Frontiers in Chemistry, 2023)
Nocaviogua A (1) and B (2), two lipolanthines featuring a noncanonical avionin (Avi)containing macrocycle and a long acyl chain, were identified from mutualistic actinomycete Nocardia sp. XZ19_369 which was isolated from nodules of sea-buckthorn collected in Tibet. Their planar structures were elucidated via extensive analyses of 1D and 2D NMR, as well as HRMS data.The absolute configurations were fully elucidated by advanced Marfey's analysis and GIAO NMR calculations, representing the first time that the configurations of this family of lipolanthines have been determined. Nocaviogua A (1) exhibited weak cytotoxicity against human chronic uveal melanoma cells (UM92-1), non-small cell lung cancer (NCI-H2170) and breast cancer (MDA-MB-231). Our work provides valuable information on this burgeoning class of lipolanthines for further investigations.